2002
DOI: 10.1051/0004-6361:20011541
|View full text |Cite
|
Sign up to set email alerts
|

Low-extinction windows in the inner Galactic Bulge

Abstract: Abstract. We built K band extinction maps in the area of two candidate low-extinction windows in the inner Bulge: W0.2-2.1 at ( , b) = (0.25• , −2.15 • ), and W359.4-3.1 at ( , b) = (359.40• , −3.10 • ). We employed JHKs photometry from the 2MASS Point Source Catalog. Extinction values were determined by fitting the upper giant branch found in the present 2MASS Ks (J −Ks) diagrams to a de-reddened bulge stellar population reference giant branch. We tested the method on the well known Baade's and Sgr I windows:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
158
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(165 citation statements)
references
References 28 publications
6
158
1
Order By: Relevance
“…Photometric data were downloaded for objects of a field located in Baade's window, we extracted photometry for an area of Δα × Δδ ≈ 0.5 • × 1 • . Only stars fulfilling σ JHK < 0.05 mag were chosen, the correction for interstellar reddening was carried out according to the extinction values given by Dutra et al (2002). The 2MASS photometry had to be transformed to our Bessell system using the equations given in Carpenter (2001; see their Appendix A).…”
Section: Appendix A: Various Comparative Datamentioning
confidence: 99%
“…Photometric data were downloaded for objects of a field located in Baade's window, we extracted photometry for an area of Δα × Δδ ≈ 0.5 • × 1 • . Only stars fulfilling σ JHK < 0.05 mag were chosen, the correction for interstellar reddening was carried out according to the extinction values given by Dutra et al (2002). The 2MASS photometry had to be transformed to our Bessell system using the equations given in Carpenter (2001; see their Appendix A).…”
Section: Appendix A: Various Comparative Datamentioning
confidence: 99%
“…The best fit isochrone then gives the value of apparent distance-modulus as 10.80.3 mag and 11.30.2 mag for NGC 110 and DOLIDZE 14, respectively. The reddening correction has been obtained by the absorption formula A H /A V = 0.176 as suggested by Dutra et al (2002). The distance of each cluster is then determined through the following relation:…”
Section: Colour-magnitude Diagrams: Distance Age and Colour-excessmentioning
confidence: 99%
“…The main photometrical parameters (age, distance, and reddening) are determined for our clusters by fitting the 2MASS ZAMS solar metallicity isochrones of Marigo et al (2008) The observed data has been corrected for interstellar reddening using the coefficients ratios AJ AV = 0.276 and AH AV = 0.176, which were derived from absorption rations of Schlegel et al (1998), while the ratio AK s AV = 0.118 was derived from Dutra et al (2002). 1.…”
Section: Colour-magnitude Diagramsmentioning
confidence: 99%
“…The main photometrical parameters (age, distance, and reddening) are determined for our clusters by fitting the 2MASS ZAMS solar metallicity isochrones of The observed data has been corrected for interstellar reddening using the coefficients ratios AJ AV = 0.276 and AH AV = 0.176, which were derived from absorption rations of Schlegel et al (1998), while the ratio AK s AV = 0.118 was derived from Dutra et al (2002). Once the cluster's distance R ⊙ is estimated, then the distance from the galactic centre (R G ) and the projected distances on the galactic plane from the Sun (X ⊙ & Y ⊙ ) and the distance from galactic plane (Z ⊙ ) can be determined, (for more details about the distances calculations, see Tadross 2011).…”
Section: Colour-magnitude Diagramsmentioning
confidence: 99%